Consumer behavior and analytics - Smith, Andrew, 1967 March 27- (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"The 2nd edition of Consumer Behaviour and Analytics provides a consumer behaviour textbook for the new marketing reality. In a world of Big Data, machine learning and artificial intelligence, this key text reviews the issues, research and concepts essential for navigating this new terrain. It demonstrates how we can use data-driven insight and merge this with insight from extant research to inform knowledge-driven decision-making. Adopting a practical and managerial lens, while also exploring the rich lineage of academic consumer research, this textbook approaches its subject from a refreshing and original standpoint. It contains numerous accessible examples, scenarios and exhibits and condenses the disparate array of relevant work into a workable, coherent, synthesized and readable whole. Providing an effective tour of the concepts and ideas most relevant in the age of analytics-driven marketing (from data visualization to semiotics), the book concludes with an adaptive structure to inform managerial decision-making. Consumer Behaviour and Analytics provides a unique distillation from a vast array of social and behavioural research merged with the knowledge potential of digital insight. It offers an effective and efficient summary for undergraduate, postgraduate or executive courses in consumer behaviour and marketing analytics, and also functions as a supplementary text for other marketing modules. Online resources include PowerPoint slides"--
OCLC-licensed vendor bibliographic record.
Keywords: Consumer behavior; Marketing -- Data processing; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Consumer Behavior; BUSINESS & ECONOMICS / Decision-Making & Problem Solving